MARRIAGE MIGRATION: THE CASE OF FEMALE MIGRANTS IN KOREA - Rahimberdiyev Sardorbek Bekmurod o‘g’li; No‘Monov Kamronbek Kozimjon o‘g’li; Jaxongir Rustamaliyev Fakhriddin o‘g’li (Web of Journals Publishing, 2025)
This article examines the exact number of migrants who have visited the Republic of Korea from many countries between 1990 and 2020. It also examines the immigration policies and demographic changes in the society implemented by the Republic of Korea, as well as the number of female and male immigrants coming to the Republic of Korea through the F-6 marriage visa and the E-9 unskilled worker visa. It scientifically analyzes the increasing demand for female migrants in society due to the changing role of women in Korean society.
Keywords: F-6, E-9, Republic of Korea, demographics, feminization, migrant, gender, DESA.